Genomic screening of new putative antiviral lectins from Amazonian cyanobacteria based on a bioinformatics approach. Issue 10 (25th September 2018) - Siqueira, Andrei Santos; Lima, Alex Ranieri Jerônimo; Aguiar, Delia Cristina Figueira; Santos, Alberdan Silva; Vianez Júnior, João Lídio da Silva Gonçalves; Gonçalves, Evonnildo Costa
Abstract: Lectins are proteins of nonimmune origin, which are capable of recognizing and binding to glycoconjugate moieties. Some of them can block the interaction of viral glycoproteins to the host cell receptors acting as antiviral agents. Although cyanobacterial lectins have presented broad biotechnological potential, little research has been directed to Amazonian Cyanobacterial diversity. In order to identify new antiviral lectins, we performed genomic analysis in seven cyanobacterial strains from Coleção Amazônica de Cianobactérias e Microalgas (CACIAM). We found 75 unique CDS presenting one or more lectin domains. Since almost all were annotated as hypothetical proteins, we used homology modeling and molecular dynamics simulations to evaluate the structural and functional properties of three CDS that were more similar to known antiviral lectins. Nostoc sp. CACIAM 19 as well as Tolypothrix sp. CACIAM 22 strains presented cyanovirin‐N homologues whose function was confirmed by binding free energy calculations. Asn, Glu, Thr, Lys, Leu, and Gly, which were described as binding residues for cyanovirin, were also observed on those structures. As for other known cyanovirins, those residues in both our models also made favorable interactions with dimannose. Finally, Alkalinema sp. CACIAM 70d presented one CDS, which was identified as a seven‐bladed beta‐propeller structure with binding sites predicted for sialic acid and N‐acetylglucosamine. Despite its singular structure, our analysis suggested this molecule as a new putative antiviral lectin. Overall, the identification and the characterization of new lectins and their homologues are a promising area in antiviral research, and Amazonian cyanobacteria present biotechnological potential to be explored in this regard.